Method for producing hollow particles and hollow particles

JP2026169339APending Publication Date: 2026-10-16DAIKIN INDUSTRIES LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2026183774
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-16

Smart Images

  • Figure 2026169339000001
    Figure 2026169339000001
  • Figure 2026169339000002
    Figure 2026169339000002
Patent Text Reader

Abstract

This disclosure aims to solve the problem of making the number of pores and volume fraction of hollow microparticles more consistent in the manufacturing of hollow microparticles. It also aims to solve the problem of increasing the types of polymers that can be used by eliminating the polymerization reaction. [Solution] A method for producing hollow microparticles according to the present disclosure comprises the steps of (1) obtaining an emulsion by emulsifying a polymer solution in an aqueous solution containing a surfactant, and (2) obtaining hollow microparticles by drying the emulsion obtained in step (1), wherein the polymer solution comprises (A) at least one solvent having a logP or ClogP of 0.5 or higher; (B) at least one solvent having a higher boiling point than solvent (A); and (C) at least one polymer soluble in solvent (A).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a method for producing hollow microparticles and to hollow microparticles. [Background technology]

[0002] The following are examples of conventional methods for manufacturing hollow microparticles. Patent Document 1 discloses a manufacturing method consisting of the following three steps. Step 1: Prepare an aqueous solution containing a dissolved surfactant. Step 2: Disperse the solution, which is obtained by dissolving the resin precursor in a solvent to a concentration of 40% by weight or less, into the aqueous solution from Step 1 in which the surfactant is dissolved, and then immediately dilute it with water. Step 3: The solvent is removed and the precursor is polymerized to form hollow resin particles.

[0003] Patent Document 2 discloses a manufacturing method comprising the following steps: a step of dispersing encapsulated microparticles in an aqueous solution containing a microparticle-forming substance to form a dispersed phase; a step of releasing droplets of the dispersed phase into a lipophilic continuous phase via a membrane member having a predetermined pore size to form a water-in-oil emulsion; a step of adding a crosslinking agent to the water-in-oil emulsion to crosslink the microparticle-forming substance to form microparticles containing encapsulated microparticles; and a step of immersing the microparticles containing encapsulated microparticles in a solvent capable of dissolving encapsulated microparticles to form hollow microparticles having at least one hollow pore and an average particle size of 0.1 μm to 10 μm.

[0004] Patent Document 3 discloses a method for producing hollow fine particles containing a fluorine-containing resin, characterized by comprising the steps of dispersing a solution containing a fluorine-containing monomer, an oil-soluble initiator, and a non-polymerizable solvent in water containing a fluorine-containing surfactant, and polymerizing the fluorine-containing monomer to obtain hollow fine particles. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2009-263553 [Patent Document 2] Japanese Patent Publication No. 2010-214219 [Patent Document 3] Japanese Patent Publication No. 2020-183500 [Overview of the Initiative] [Problems that the invention aims to solve]

[0006] However, conventional methods for producing hollow microparticles have the following problems. First, the methods for producing hollow microparticles described in Patent Documents 1 and 3 require a monomer polymerization reaction. Therefore, polymers that cannot be polymerized in a dispersion medium cannot be used.

[0007] Furthermore, in the manufacturing method described in Patent Document 2, the core portion of the core-shell structure obtained as an intermediate is solid, making it difficult to control the number of pores. Specifically, because the number of core particles incorporated into the polymerization solvent microparticles containing the core material cannot be controlled, the shape, number of pores, volume fraction, and film thickness are not constant, resulting in the problem of difficulty in achieving stable performance. [Means for solving the problem]

[0008] [1] (1) (A) At least one solvent having a logP or ClogP of 0.5 or higher; (B) at least one solvent having a higher boiling point than solvent (A); and (C) At least one polymer soluble in the solvent (A) A step of obtaining an emulsion by emulsifying a polymer solution containing a surfactant in an aqueous solution; and (2) A step to obtain hollow fine particles by removing the dispersion medium and solvent (B) from the emulsion obtained in step (1) above. A method for producing hollow microparticles, including [the specified term].

[0009] [2] The method for producing hollow fine particles according to [1], wherein in the step (2), the hollow fine particles are obtained via a core-shell structure that contains the solvent (B) in the core and the polymer (C) in the shell.

[0010] [3] The method for producing hollow fine particles according to [1] or [2], wherein in the step (2), the dispersion medium and the solvent (B) are removed by freeze drying, heat drying, or vacuum drying.

[0011] [4] The main chain of the polymer (C) is: one or more groups selected from the group consisting of siloxane, amide, imide, ester, ether, sulfonyl, sulfone, and ketone; or a cyclic structure The method for producing hollow fine particles according to any one of [1] to [3], comprising the same.

[0012] [5] The method for producing hollow fine particles according to any one of [1] to [4], wherein the polymer (C) is at least one polymer selected from the group consisting of polydialkylsiloxane, polyphenylene ether, polyamide, polyetherimide, polyimide, polyamideimide, polyester, polycarbonate, polyacetal, polyaryletherketone, polysulfone, polyethersulfone, and cycloolefin polymer.

[0013] [6] The method for producing hollow fine particles according to any one of [1] to [5], wherein the polymer (C) is polydimethylsiloxane or polyimide.

[0014] [7] The method for producing hollow fine particles according to any one of [1] to [6], wherein the boiling point of the solvent (A) at normal temperature and normal pressure is 100°C or lower.

[0015] [8] The method for producing hollow fine particles according to any one of [1] to [7], wherein the logP or ClogP of the solvent (A) is 1 to 3.

[0016] [9] The method for producing hollow fine particles according to any one of [1] to [8], wherein the solvent (A) is at least one solvent selected from the group consisting of fluoroethers, chloroform, and dichloromethane.

[0017]

[10] The method for producing hollow fine particles according to any one of [1] to [9], wherein the solvent (B) is perfluorocarbons.

[0018]

[11] Hollow fine particles, wherein the shell comprises a polymer that is soluble in a solvent having a logP or ClogP of 0.5 or more.

[0019]

[12] The main chain of the polymer is: One or more groups selected from the group consisting of amide, imide, ester, ether, sulfonyl, sulfone, and ketone; or Cyclic structure The hollow fine particles according to

[11] , comprising the same.

[0020]

[13] The hollow fine particles according to

[11] or

[12] , wherein the polymer is at least one polymer selected from the group consisting of polydialkylsiloxane, polyphenylene ether, polyamide, polyetherimide, polyimide, polyamideimide, polyester, polycarbonate, polyacetal, polyaryl ether ketone, polysulfone, polyether sulfone, and cycloolefin polymer.

[0021]

[14] The hollow fine particles according to any one of

[11] to

[13] , wherein the polymer is at least one polymer selected from the group consisting of polyester, polyamide, polyamideimide, polyimide, polyetherimide, and polycarbonate.

[0022]

[15] The hollow fine particles according to any one of

[11] to

[14] , wherein the polymer is polydimethylsiloxane or polyimide.

[0023]

[16] Hollow fine particles according to any one of

[11] to

[15] , wherein the boiling point of the solvent at room temperature and pressure is 100°C or less.

[0024]

[17] Hollow fine particles according to any one of

[11] to

[16] , wherein the logP or ClogP of the solvent is 1 to 3.

[0025]

[18] The hollow fine particle according to any one of

[11] to

[17] , wherein the solvent is at least one solvent selected from the group consisting of fluoroethers, chloroform, and dichloromethane.

[0026]

[19] Hollow fine particles according to any of

[11] to

[18] , wherein the average particle size is 1 μm to 50 μm.

[0027]

[20] Hollow fine particles according to any one of

[11] to

[19] , wherein the thickness of the shell is 0.01 μm to 20 μm.

[0028]

[21] Hollow fine particles according to any of

[11] to

[20] , wherein the volume fraction of the shell layer constituting the particle is 50% or less.

[0029]

[22] Hollow microparticles according to any one of

[11] to

[21] , wherein the number of voids in the particle is 1 or 2.

[0030]

[23] In total on the surface and interior of the shell, and in the core: (A) At least one solvent with a logP or ClogP of 0.5 or higher; and / or (B) At least one solvent having a higher boiling point than solvent (A) Hollow particles as described in any of

[11] to

[23] , comprising a total of 0% to 1% by weight. [Effects of the Invention]

[0031] This disclosure provides a method for producing hollow microparticles that solves the above problems, and allows for easier control of the volume fraction and film thickness of the shell layer compared to the conventional technology. Furthermore, it enables the use of a wider variety of polymers compared to the conventional technology. [Modes for carrying out the invention]

[0032] An embodiment of this disclosure will be described in detail below, but the scope of this disclosure is as described here. This invention is not limited to one embodiment, and various modifications can be made without departing from the spirit of this disclosure. Furthermore, if multiple upper and lower limits are given for a particular parameter, any combination of these upper and lower limits can be used to create a suitable numerical range.

[0033] Method for manufacturing hollow microparticles In this disclosure, "hollow microparticle" means a particle having a pore inside that is not connected to the outside. The shape of the pore may be spherical or not. The number of pores may be one or more.

[0034] The method for producing hollow microparticles in this disclosure is: (1) (A) At least one solvent having a logP or ClogP of 0.5 or higher; (B) at least one solvent having a higher boiling point than solvent (A); and (C) At least one polymer soluble in the solvent (A) A step of obtaining an emulsion by emulsifying a polymer solution containing a surfactant in an aqueous solution; and (2) A step to obtain hollow fine particles by removing the dispersion medium and solvent (B) from the emulsion obtained in step (1) above. Includes.

[0035] In the polymer solution, the polymer (C) is dissolved in a solvent (A) which has a certain degree of hydrophobicity (logP or ClogP of 0.5 or higher), and the solution also contains a solvent (B) with a higher boiling point than solvent (A). Therefore, in step (1) to obtain an emulsion by emulsifying the polymer solution in an aqueous solution containing a surfactant, a liquid-liquid core-shell phase separation structure is obtained in which the shell contains solvent (A) and polymer (C) and the core contains solvent (B). Furthermore, in step (2), by removing at least the solvent (B) of the core in addition to the dispersion medium, hollow fine particles with a hollow core are obtained. Here, "remove" does not necessarily mean completely removing the dispersion medium and solvent (B) as long as the hollow fine particles are obtained, but includes leaving some of them remaining. In the above core-shell phase separation structure, the solvent (A) may be contained in the swollen shell. It is possible.

[0036] In step (1), a polymer solution containing solvent (A), solvent (B), and polymer (C) is emulsified to obtain a core-shell structure containing these three components. Therefore, none of these three components separate, and a single phase is formed. Such a single phase can be formed, for example, by the miscibility of solvent (A) and solvent (B), or by the solubility of polymer (C) in both solvent (A) and solvent (B). The selection of these three components can be carried out appropriately in accordance with the above guidelines.

[0037] Thus, the manufacturing method of this disclosure allows for the production of hollow microparticles without a polymerization reaction. In the manufacturing process of hollow microparticles, if a polymerization reaction is required, it must be carried out in a dispersion medium. Therefore, polymers that cannot undergo polymerization in a dispersion medium cannot be used. This disclosure eliminates this problem, allowing for the separation of polymer design and particle design. This significantly increases the range of choices for the type of polymer used for the shell. In other words, it becomes possible to separate the polymer design from the hollow particle design. Furthermore, because it proceeds through a liquid-liquid core-shell structure, the shape of the hollow microparticles approaches that of a perfect sphere with a single pore. Moreover, the manufacturing method of this disclosure allows for control of shape, pore count, volume fraction, and film thickness. Additionally, by controlling the amount of polymer, it is possible to create particles with depressions during the solvent removal process. It is also possible to create children.

[0038] The surfactant is not particularly limited, and conventionally known surfactants used for emulsion formation can be suitably used. Examples include polyvinyl alcohol; and Pluronic® surfactants, which are block copolymers of polyethylene oxide and polypropylene oxide.

[0039] The type and concentration of surfactant used affect the size of the core-shell structure. Specifically, a lower surfactant concentration tends to result in a larger core-shell structure. Furthermore, the concentration of the surfactant in the aqueous solution is preferably 0.01 to 10% by weight, and more preferably 0.1 to 3% by weight, relative to the total weight (100% by weight) of the aqueous solution (aqueous solvent and surfactant).

[0040] The emulsification method is not particularly limited and can be broadly applied. Examples of emulsification methods include membrane emulsification using porous membranes such as siluscous porous glass, mechanical emulsification using homogenizers, and continuous emulsification, which involves handling these methods continuously. The emulsification temperature can be freely selected within a range that does not exceed the boiling point of the solvent used in the emulsification environment.

[0041] As an emulsification method, membrane emulsification is preferred because it yields a more homogeneous core-shell structure. By going through a more homogeneous core-shell structure, it becomes easier to obtain more homogeneous hollow fine particles by the manufacturing method disclosed herein.

[0042] Examples of membrane emulsification methods include the following membrane emulsification method using porous membranes. Step (i): A step to obtain an emulsion by membrane emulsifying the above polymer solution (dispersed phase) in an aqueous solution containing a surfactant (continuous phase) through a porous membrane having a uniform pore size. Step (ii): A step of removing the solvent (A) contained in the emulsion to form core-shell type microparticles comprising a shell containing the polymer (C) and a core containing the solvent (B).

[0043] In step (i), a polymer solution containing solvent (A), solvent (B), and polymer (C) is first prepared as a dispersed phase. By adjusting the ratio of solvent (B), which forms the core, to polymer (C), which forms the shell, the thickness of the shell in the resulting core-shell structure can be controlled.

[0044] Next, the dispersion prepared as the dispersed phase is injected into the continuous phase containing the surfactant through a porous membrane, for example by applying pressure using nitrogen gas, and emulsified through the membrane. Specifically, the dispersed phase, which is the oil (O) layer, is pushed through the porous membrane into the continuous phase, which is the water (W) phase, forming an O / W emulsion. The size of the formed emulsion is uniform (monodisperse), correlated with the uniform pore size of the porous membrane. Furthermore, since the size of the formed emulsion is proportional to the pore size of the porous membrane, it is possible to control the size of the formed emulsion, and thus the size of the microparticles (particle diameter), by adjusting the pore size of the porous membrane. It is preferable to maintain the volume ratio of the dispersed phase to the continuous phase (dispersed phase / continuous layer) at 1 / 2 to 1 / 1000 (more preferably 1 / 5 to 1 / 100, and especially preferably about 1 / 10).

[0045] The porous membrane is not particularly limited as long as it has a uniform pore size, and a variety of materials can be used, such as glass, polycarbonate or other resins, or metal. The pore size of the porous membrane can be determined according to the desired size of the microparticles, but usually, a porous membrane with a pore size in the range of 0.05 to 20 μm (preferably 2 to 10 μm) can be used.

[0046] Furthermore, membrane emulsification is preferably performed under stirring in order to separate the droplets from the membrane surface.

[0047] In step (ii), the solvent (A) in the emulsion obtained in step (i) is removed by evaporation. During the evaporation process, phase separation occurs between the shell component (O phase) containing the polymer (C), the core component (F phase) containing the solvent (B), and the continuous phase (W phase), forming core-shell type particles having a shell containing the polymer (C) and a core containing the solvent (B).

[0048] In step (2), hollow fine particles can be obtained by further removing solvent (B) from the core-shell structure that contains solvent (B) in addition to the dispersion medium.

[0049] In step (2), the method for removing the dispersion medium and solvent (B) from the emulsion is not particularly limited and can be carried out by drying, for example. For example, since it is difficult to remove solvent (B) from the core by natural drying, it is preferable from an efficiency standpoint to adopt a drying method that is more effective in removing solvent (B). Such drying methods include methods that dry forcibly rather than naturally, such as freeze-drying, heat drying, vacuum drying, or reduced-pressure drying. Even with natural drying, it is possible to remove solvent (B) from the core by adjusting conditions such as temperature and / or humidity, or by allowing a longer drying time.

[0050] For freeze-drying, it is preferable to reduce the pressure to near vacuum, where the boiling points of the coexisting water and solvent are lowered. More preferably, conditions are in place that allow the solvent to sublimate in order to suppress the destruction of hollow particles due to the expansion of the core liquid. Such conditions can be set appropriately depending on the type of solvent, etc.

[0051] In the manufacturing method disclosed herein, water and surfactants contained in the starting materials can be removed after step (1) or after step (2). For example, when removed after step (1), water and surfactants exist as a continuous phase outside the core-shell structure. In this case, the method for removing this continuous phase is not particularly limited and can be appropriately selected depending on the relationship between the continuous phase and the core-shell structure. For example, if the core is sufficiently hydrophobic, the continuous phase can be easily removed. On the other hand, if the core is relatively hydrophilic and the surface of the core is swollen with water, it can be removed by drying. If water and surfactants remain after step (2), they can be removed, and the method for doing so can be the same as described above.

[0052] Polymer (C) may be used alone or in combination of two or more types.

[0053] The polymer (C) can be any polymer soluble in solvent (A), and its structure is not particularly limited. It is obvious that the structure is not limited, as long as it can solidify by drying after being dissolved in solvent (A), hollow fine particles will be formed. Furthermore, since polymer (C) forms the structure of hollow fine particles, it needs to have physical properties that allow the structure to be maintained, and specifically it has a melting point of 70°C or higher, preferably 80°C or higher, more preferably 90°C, and even more preferably 100°C or higher. In addition, it has a glass transition temperature of 120°C or higher, preferably 130°C, more preferably 140°C, and even more preferably 150°C or higher.

[0054] The type of polymer (C) is not particularly limited, but can be broadly selected from polymers synthesized by chain polymerization, stepwise polymerization, or living polymerization, as long as the above solvent solubility requirements are met. These may be copolymers and are not particularly limited; random copolymerization, alternating copolymerization, block copolymerization, or graft copolymerization can all be used.

[0055] Chain polymerization is a process in which an active species obtained from a monomer reacts with the monomer to grow a molecular chain. These are reactions such as radical polymerization, anionic polymerization, cationic polymerization, coordination polymerization, and ring-opening polymerization. Examples of polymers include vinyl polymers, acrylic polymers, nylon polymers, and cycloolefin polymers. Examples of polymers include polystyrene, polymethyl methacrylate, polyvinyl halide, fluorinated vinyl monomer (such as tetrafluoroethylene)-vinyl monomer (such as vinyl acetate and vinylpyrrolidone) copolymers, and Zeonex manufactured by Nippon Zeon.

[0056] Stepwise polymerization is a reaction in which molecular chains grow as reaction sites of monomers bond together, and specific examples include polycondensation and addition condensation. Examples of polymers include polyamides, polyetherimides, polyimides, polyamideimides, polyesters, polycarbonates, polyaryletherketones, polysulfones, polyethersulfones, and phenolic resins.

[0057] A condensation polymer refers to a polymer synthesized by repeated condensation or addition between bifunctional compounds. Examples of reactions used in synthesis include polycondensation reactions, polyaddition reactions, and polyaddition-condensation reactions. In this disclosure, it is preferable to use a condensation polymer as polymer (C) because it exhibits superior mechanical properties in terms of the physical properties of the resulting hollow fine particles.

[0058] Examples of homopolymers include acrylic polymers.

[0059] The homopolymers and copolymers preferably have a main chain that includes one or more groups selected from the group consisting of ethers and ketones; or a cyclic structure.

[0060] The copolymer polymer (C) may be an alternating copolymer, a random copolymer, a block copolymer, or a graft copolymer.

[0061] Examples of cyclic structures include aromatic rings such as benzene rings and non-aromatic rings such as cyclohexane, which may have one or more substituents. Examples of non-aromatic rings include aliphatic 4- to 12-membered rings, preferably aliphatic 4- to 7-membered rings. More specific examples include pyrrolidone.

[0062] Examples of substituents include halogen atoms such as fluorine, chlorine, bromine, and iodine, as well as hydroxyl groups, mercapto groups, amino groups, nitro groups, and cyano groups. The number of substituents is, for example, one or more, less than or equal to the maximum number of substituents that can be substituted (e.g., two, three, four, or five).

[0063] Examples of homopolymer polymers (C) include polyphenylene ethers, polyacetals, and cycloolefin polymers.

[0064] As a condensation polymer, it is preferable that the main chain contains one or more groups selected from the group consisting of amides, imides, esters, sulfonyls, and sulfones.

[0065] Examples of polymers (C) that are condensation polymers include polyamides, polyetherimides, polyimides, polyamideimides, polyesters, polycarbonates, polyaryletherketones, polysulfones, polyethersulfones, polycaprolactones, and polycaprolactams.

[0066] Preferred polymers (C), which are condensation polymers, include polyamides, polyetherimides, polyimides, polyamideimides, polyesters, and polycarbonates.

[0067] In particular, polyimide is preferred as the polymer (C), which is a condensation polymer.

[0068] Specific examples of condensation polymers include, for example, fluorine-containing polyimides such as 4,4'-[perfluoropropane-2,2'-diyl]diphthalic anhydride / 2,2'-bis(trifluoromethyl)-4,4'diaminobiphenyl alternating copolymer, solvent-soluble polyimides and polyamides represented by Kawamura Industries' KPI-MX300F and Somar's Spixeria, solvent-soluble polycarbonates represented by Mitsubishi Gas Chemical's Yupizeta, and solvent-soluble polyesters represented by Toyobo MC's Byron.

[0069] Examples of polyamides include aliphatic polyamides, semi-aromatic polyamides, and aromatic polyamides.

[0070] Examples of polyimides include those containing the following structure as repeating units. [ka] (In the formula, R 1 This represents an aromatic ring structure, R 1 Each of these groups forms a ring of 5 or 6 atoms with the adjacent imide group. R 1 While it is not particularly limited to containing aromatic structures as long as solvent solubility can be ensured, the following formula: [ka] It is preferable that the group is represented by (Rf 1~2 (These represent identical or different perfluoroalkyl groups having 1 to 10 carbon atoms.) R 2 NH2-R 2 -NH2 represents the carbon chain portion of a diamine, where n is 1 or greater. It is an integer.

[0071] R 2 While not particularly limited, it can be a fluorine-containing alkyl chain having 1 to 30 carbon atoms, and may be branched or contain ether functional groups in the main chain. 2 The internal structure may include multiple repeating units.

[0072] Examples of polyesters include polycaprolactone (PCL) and polylactic acid (PLA). Polyhydroxybutyrate (PHB), polyglycolic acid (PGA), polyethylene adipate (PEA), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) Polyethylene naphthalate (PEN), polytrimethylene terephthalate (PTT), polyester of 4-hydroxybenzoic acid and 6-hydroxynaphthalene-2-carboxylic acid (LCP), and polyester of bisphenol A and phthalic acid (PAR) can be used.

[0073] Polymer (C) is preferably soluble in solvent (A) while retaining its mechanical properties, and therefore preferably has a molecular weight of 1,000 to 1,000,000, more preferably 1,500 to 500,000, and even more preferably 2,000 to 1,000,000. In practice, a suitable soluble polymer (C) can be selected depending on the type of solvent (A).

[0074] Depending on the function to be imparted to the resulting hollow microparticles, the polymer (C) can be, for example, a fluorine-containing polymer. In this case, due to the low intermolecular attractive forces and low surface free energy of the fluorine-containing polymer, the hollow microparticles of this disclosure can be dispersed in an aqueous medium. Furthermore, the fluorine-containing polymer has excellent stability to acids, alkalis, and hot water, and also exhibits excellent long-term stability in water. In addition, it has the advantage of less microbial growth on a smooth surface. For this reason, the type of fluorine-containing polymer is not particularly limited. For example, some of the polymers described above may contain fluorine atoms.

[0075] The boiling point of the solvent (A) at normal temperature and normal pressure is preferably 150°C or lower, more preferably 130°C or lower, and even more preferably 100°C or lower.

[0076] The logP or ClogP of the solvent (A) is preferably from 1 to 3.

[0077] logP is a type of physical property value representing the hydrophobicity of a molecule. Specifically, it is the concentration ratio of both phases when a compound is dissolved in a mixture of water and 1-octanol and reaches equilibrium, that is, the partition coefficient P=C 1-octanol / C water quantified by the common logarithm. Octanol is considered to be similar in properties to biological membranes whose hydroxyl groups similarly have hydrogen bond donating and accepting abilities. A larger value indicates a substance with higher hydrophobicity, that is, higher lipophilicity.

[0078] Note that ClogP is one of the predicted values of LogP, and is specifically obtained by experimental measurement or computational estimation. In principle, since the LogP value of a molecule is basically additive, parameters for each substituent are determined based on a large number of measured values to predict the value of the entire molecule. Furthermore, parameters related to intramolecular interactions (such as intramolecular hydrogen bonds and steric effects) that disrupt additivity are also supplemented, and the latest version adds a function to predict parameters even for substituents with no existing parameters, so predicted values can be output for all given structures. For estimation, commercially available parameter prediction software can be used, and in the present disclosure, the chemoinformatics library "RDKit" is used.

[0079] Solvent (A) may be used alone or in combination of two or more. In the case of a mixed solvent, it is preferable that the ClogP of the mixed solvent as a whole is 0.5 or higher and within the above preferred range. A mixed solvent as used herein refers to a solvent obtained by mixing two or more solvents in amounts that clearly exceed the level generally considered to be impurities (generally on the order of ppm).

[0080] As solvent (A), aprotic polar solvents, nonpolar solvents, low polar solvents, alcohol-based solvents, and fluorinated solvents are preferred. Examples of aprotic polar solvents include N,N-dimethylformamide, acetonitrile, dimethyl sulfoxide, hexamethyl phosphate triamide, N-methylpyrrolidone, ethyl acetate, dimethyl carbonate, acetone, methyl ethyl ketone, tetrahydrofuran, and dioxane. Examples of nonpolar solvents include carbon tetrachloride, benzene, toluene, hexane, and cyclohexane. Examples of low polar solvents include diethyl ether, monoglyme, dichloromethane, and chloroform. Examples of alcohol-based solvents include methanol, ethanol, and 1-propanol. Examples of fluorinated solvents include 2-propanol, ethylene glycol, glycerin, and mannitol. Examples of fluorinated solvents include perfluorohexane, perfluorobenzene, hydrofluoroethers represented by methoxynononafluorobutane, perfluorocrown ethers, 1-bromoheptadecafluorooctane, 1-bromotridecafluorohexane, perfluorodecalin, hexafluoroisopropanol, and 2-perfluorohexylethanol.

[0081] If solvent (A) is a single solvent, its own logP or ClogP must be 0.5 or higher. Such solvents can be appropriately selected from the above group of solvents. For example, nonpolar and low polar solvents can be used alone. Other solvents that can be used alone include ethyl acetate, dichloromethane, chloroform, perfluorohexane, perfluorobenzene, hydrofluoroethers such as methoxynononafluorobutane, 1-bromoheptadecafluorooctane, 1-bromotridecafluorohexane, perfluorodecalin, hexafluoroisopropanol, and 2-perfluorohexylethanol.

[0082] Solvent (B) may be used alone or in combination of two or more types. If it is a mixed solvent, solvent (B) as a whole has a higher boiling point than solvent (A).

[0083] When solvent (B) is a single solvent, it is sufficient that it has a higher boiling point than solvent (A), and is not particularly limited. The boiling point difference between solvent (B) and solvent (A) is preferably 10 to 200°C, more preferably 30 to 180°C, and even more preferably 40 to 150°C.

[0084] Examples of solvent (B) include fluorocarbons. In this disclosure, "fluorocarbon" means an organofluorine compound having a carbon-fluorine bond. Examples of fluorocarbons include perfluorooctyl bromide, perfluorodecalin, perfluoromethyldecalin, perfluorooctane, perfluorononane, perfluorodecane, perfluorododecane, perfluorotridecane, perfluorotributylamine, perfluorobutyltetrahydrofuran, and perfluoroadamantane.

[0085] Solvent (B) is preferable to have higher hydrophobicity than solvent (A), i.e., a higher logP or ClogP, in that it facilitates the formation of a core-shell structure in step (1). This is because, since the product obtained in step (1) is an aqueous emulsion, if solvent (B) is more hydrophobic than solvent (A), solvent (B) is more likely to be oriented towards the core. In particular, when the boiling point difference between solvent (A) and solvent (B) is smaller, solvent (B) tends to be less likely to be oriented towards the core; therefore, in this case, it is more preferable for solvent (B) to be more hydrophobic than solvent (A). Such combinations of solvent (A) and solvent (B) can be appropriately determined in accordance with the above guidelines.

[0086] hollow particles The hollow microparticles of this disclosure are hollow microparticles comprising a polymer whose shell is soluble in a solvent with a logP or ClogP of 0.3 or higher, more preferably 0.4 or higher, and even more preferably 0.5 or higher.

[0087] The hollow microparticles disclosed herein are obtained by the method for producing the hollow microparticles disclosed herein.

[0088] As described above, the method for producing hollow microparticles in this disclosure has the advantage of being able to produce hollow microparticles without undergoing a polymerization reaction. Since the hollow microparticles in this disclosure are obtained by such a manufacturing method, in the shell, the polymer (C) is not crosslinked with each other, or the degree of crosslinking is lower compared to those obtained by conventional methods that involve a polymerization reaction. For this reason, conventional The shells obtained by the polymerization reaction described above cannot be dissolved in solvents with a logP or ClogP of 0.5 or higher because the polymers are crosslinked, whereas the hollow microparticles of the present disclosure can be dissolved in the above solvents. Therefore, the hollow microparticles of the present disclosure have the advantage that the hollow microparticles of the present disclosure can be reconstituted using the polymer dissolved as described above.

[0089] The hollow fine particles of this disclosure preferably have an average particle size of 1 μm to 50 μm, more preferably 2 μm to 45 μm, and even more preferably 3 μm to 40 μm.

[0090] In this disclosure, the average particle diameter of hollow microparticles refers to the number-average particle diameter and is measured as follows. It can be measured using a laser diffraction particle size distribution analyzer or the like.

[0091] The hollow microparticles in this disclosure only need to have a shell thickness that does not exceed the particle radius, preferably 0.01 μm to 20 μm, more preferably 0.02 μm to 19 μm, and even more preferably 0.03 μm to 17 μm. In this disclosure, the shell thickness of the hollow microparticles is measured as follows: The resulting particles are cut and the thickness is obtained by observing them with a scanning electron microscope.

[0092] The hollow microparticles in this disclosure preferably have a volume fraction of 30% to 99%, more preferably 35% to 95%, and even more preferably 40% to 90%. The shape of the voids is not particularly limited, but can be spherical, ellipsoidal, rod-shaped, ant-nest-like, etc. In the case of hollow microparticles produced by emulsification, preferably 50% or more, more preferably 70% or more, and even more preferably 80% or more can be spherical voids. In this disclosure, the volume fraction of the hollow microparticles is calculated as follows. The volume of the voids can be calculated from the measured film thickness and particle size, and the volume fraction can be calculated by calculating the ratio to the volume of the spheres. Furthermore, in this method, since the obtained particles are almost perfectly spherical and the film thickness is almost uniform after passing through the emulsified particles, it can also be approximately calculated from the amount of polymer (C) and solvent (B) used.

[0093] Since the hollow microparticles of this disclosure are obtained by the manufacturing method of this disclosure, they are obtained via a liquid-liquid core-shell structure, and therefore, the hollow microparticles of this disclosure are preferably perfectly spherical.

[0094] For the same reasons as above, the hollow particles of this disclosure preferably have one or two voids.

[0095] Since the hollow microparticles of this disclosure are obtained by the manufacturing method of this disclosure, a more homogeneous group of hollow microparticles can be obtained, as described above, by employing, for example, membrane emulsification as the emulsification method. In this case, the group of hollow microparticles of this disclosure can have a monodisperse particle size distribution. Specifically in this case, the CV value of the group of hollow microparticles of this disclosure is preferably 70% or less, more preferably 40% or less, even more preferably 35% or less, and even more preferably 30% or less. In this disclosure, the CV value of the group of hollow microparticles is the coefficient of variation of the particle size distribution, which is determined by the standard deviation of the particle size and the volume-average particle size. A lower CV value indicates better uniformity of particle size. Specifically, the coefficient of variation CV value of the particle size distribution can be calculated by the following formula. CV value (%) = (Standard deviation of particle size / Volume-average particle size) × 100

[0096] Since the hollow microparticles of this disclosure are obtained by the manufacturing method of this disclosure, they may contain trace amounts of some of the raw materials used in the manufacturing method of this disclosure. In this case, the hollow microparticles of this disclosure have a total of: (A) at least one solvent with a logP or ClogP of 0.5 or higher; and / or (B) at least one solvent having a higher boiling point than solvent (A), in an amount of 0% to 1% by weight, preferably more than 0% by weight, and 1% by weight on the surface and interior of the shell and in the core. It contains % or less, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less. Within this numerical range, "greater than 0% by weight" means that the substance is detected beyond the detection limit of the applicable measurement method.

[0097] Because the hollow nanoparticles disclosed herein are hollow, they are considered to have excellent low dielectric properties and are therefore suitable for electrical material applications. Electrical material applications using the hollow nanoparticles disclosed herein are not limited to but include printed circuit boards, antenna substrates, and interlayer insulating films for high-frequency connectors.

[0098] The hollow microparticles disclosed herein are considered to have excellent low refractive index properties due to their hollow nature, and are applicable to various applications requiring a low refractive index. In other words, the hollow microparticles disclosed herein can be used as low refractive index materials. When used as a low refractive index material, they can be suitably used, for example, in anti-reflective films, refractive index modifiers, additive fillers for optical adhesives, low refractive index lens materials, prisms, and radiation therapy sensitizers.

[0099] Because the hollow particles disclosed herein are lightweight due to their hollow structure, they can be applied to various applications where weight reduction is required. Specifically, the hollow particles disclosed herein can be used as a metal substitute material for automobiles. Furthermore, because the hollow particles contain air, they have excellent heat insulation properties and are suitable for use as a heat insulating material.

[0100] Because the hollow particles in this disclosure are hollow, they are thought to be able to encapsulate substances and can be applied to various applications that involve absorbing substances. Specifically, the hollow microparticles in this disclosure can be suitably used as adsorbents such as desiccants, carriers such as catalysts, carriers for pharmaceuticals used in drug delivery systems, nanoparticle-encapsulated sensors, and the like.

[0101] The hollow particles disclosed herein are low in density and contain air because they are hollow, making them suitable for applications requiring weight reduction and heat insulation. In other words, the hollow fine particles disclosed herein can be suitably used as lightweight resin fillers, heat insulating materials, and heat insulating resin fillers. [Examples]

[0102] This disclosure is not limited to the following embodiments.

[0103] Example 1 (Step 1) 50 mg of 4,4'-[perfluoropropane-2,2'-diyl] Diphthalic anhydride / 2,2'-bis(trifluoromethyl)-4,4' diaminobiphenyl alternating copolymer (fluorine content 33% by weight) and 0.12 g of perfluorooctyl bromide were dissolved in 2 mL of dichloromethane (logP=1.25). Nile Red was added for fluorescence measurement. The resulting solution was then mixed with 20 mL of 2% polyvinyl alcohol. By extruding the water into an aqueous solution through a hydrophilic glass porous membrane using a syringe, membrane emulsification is achieved. This resulted in the acquisition of emulsified particles.

[0104] (Step 2) Next, while stirring the emulsion at room temperature, add dichloromethane and par Evaporate fluorooctyl bromide to obtain 4,4'-[perfluoropropane-2,2'-diyl]diphthalic anhydride / 2,2'-bis(trifluoromethyl)-4,4 Hollow microparticles composed of alternating diaminobiphenyl copolymers were obtained. The volume-average particle size was 6.63 μm. The CV value was 29%.

[0105] Comparative Example 1 The procedure was carried out except for dissolving the solution in 2 mL of acetone (logP=-0.24) as the solvent. When emulsification was performed in the same manner as in Example 1, the emulsion particles, which are precursors to hollow microparticles, could not be formed because acetone dissolved in the aqueous solution.

Claims

[Claim 1] (1) (A) At least one solvent in which logP or ClogP is 0.5 or higher; (B) at least one solvent having a higher boiling point than solvent (A); and (C) At least one polymer soluble in the solvent (A) A step of obtaining an emulsion by emulsifying a polymer solution containing a surfactant in an aqueous solution; and (2) A step to obtain hollow fine particles by removing the dispersion medium and solvent (B) from the emulsion obtained in step (1) above. A method for producing hollow microparticles, including [the specified term].

Citation Information

Patent Citations

  • Hollow resin particle

    JP2009263553A

  • Hollow fine particle, and method and apparatus for producing the same

    JP2010214219A

  • Production method of hollow fine particle and hollow fine particle

    JP2020183500A